1999
DOI: 10.1677/joe.0.1630069
|View full text |Cite
|
Sign up to set email alerts
|

Administration of growth hormone or IGF-I to pregnant rats on a reduced diet throughout pregnancy does not prevent fetal intrauterine growth retardation and elevated blood pressure in adult offspring

Abstract: Increasing evidence from human epidemiological studies suggests that poor growth before birth is associated with postnatal growth retardation and the development of cardiovascular disease in adulthood. We have shown previously that nutritional deprivation in the pregnant rat leads to intrauterine growth retardation (IUGR), postnatal growth failure, changes in the endocrine parameters of the somatotrophic axis, and to increased blood pressure in later life. In the present study, we investigated whether administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…These have uniformally been raised (Langley & Jackson, 1994;LangleyEvans et al 1996b,c;Woodall et al 1996Woodall et al , 1999Gardner et al 1997). Direct comparisons with the present study are hindered by differences in baseline pressures.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…These have uniformally been raised (Langley & Jackson, 1994;LangleyEvans et al 1996b,c;Woodall et al 1996Woodall et al , 1999Gardner et al 1997). Direct comparisons with the present study are hindered by differences in baseline pressures.…”
Section: Discussionmentioning
confidence: 54%
“…Other studies using the tail-cuff method have not observed gender differences and may reflect the lower sensitivity of the method used; Langley-Evans et al (1996c) have shown no difference in blood pressure of male and female 4-week-old offspring of proteinrestricted dams and Woodall et al (1999) considered male and female offspring together as no gender differences were apparent in offspring of control or restricted groups. Studies in 60-day-old oophorectomised offspring of the nutritionally restricted dams are planned to determine if female sex hormones offer protection against the rise in blood pressure observed in the males.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A possible alternative explanation of these differences could be the (necessary) cross-fostering of the IUGR pups (but not the control pups) onto normal dams to generate a transition from a nutritionally deprived environment before birth to a nutritionally adequate environment after birth. We chose to use the exact experimental approach employed in a number of earlier studies where considerable data are available about the IUGR phenotype Krechowec, Vickers, Gertler, & Breier, 2006;Vickers et al, 2000;Vickers et al, 2001;Woodall et al, 1999;Woodall et al, 1996) so that direct physiological comparisons could be made. Thus, it is possible (though we believe it unlikely) that the learning differences we have documented here arose fully, or partially, from crossfostering.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, IUGR offspring were provided with the same nutrient-rich environment after birth as were control offspring, and IUGR pups were cross-fostered onto control dams that had their offspring removed after birth. This experimental approach generates IUGR offspring of significantly reduced birth weight without affecting litter size (Vickers et al, 2000;Woodall et al, 1999;Woodall et al, 1996). For the present study, we used conditions identical to those reported by our laboratory for physiological, metabolic, and endocrine studies investigating the impact of maternal undernutrition during gestation on the biological phenotype of offspring.…”
Section: Methods Subjectsmentioning
confidence: 99%